2017
DOI: 10.1016/j.envexpbot.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DNA methylation patterns associated with drought stress response in faba bean ( Vicia faba L.) using methylation-sensitive amplification polymorphism (MSAP)

Abstract: Analysis of DNA methylation patterns associated with drought stress response in faba bean (Vicia faba L.) using methylation-sensitive amplification polymorphism (MSAP).Environmental and Experimental Botany http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 60 publications
3
36
2
2
Order By: Relevance
“…Similar conclusions were drawn from the epigenetic responses of clover and hemp which decreased the methylation level under chromium stress but an active de novo synthesis of methylated cytosine was found to positively correlate with the intensity of the stress in the rape genome (Aina et al, 2004;Labra et al, 2004). Nonetheless, we deduced that hypermethylation under drought stress is a tolerance strategy in sesame and it would be valuable to compare in a future experiment the epigenetic alterations of (1) several sesame genotypes with contrasting levels of drought tolerance to understand the intra-species variation (Abid et al, 2017), (2) various plant species exhibiting contrasting responses to drought to uncover the inter-species variation (Aina et al, 2004).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Similar conclusions were drawn from the epigenetic responses of clover and hemp which decreased the methylation level under chromium stress but an active de novo synthesis of methylated cytosine was found to positively correlate with the intensity of the stress in the rape genome (Aina et al, 2004;Labra et al, 2004). Nonetheless, we deduced that hypermethylation under drought stress is a tolerance strategy in sesame and it would be valuable to compare in a future experiment the epigenetic alterations of (1) several sesame genotypes with contrasting levels of drought tolerance to understand the intra-species variation (Abid et al, 2017), (2) various plant species exhibiting contrasting responses to drought to uncover the inter-species variation (Aina et al, 2004).…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, a quantification of the genome wide cytosine methylation polymorphism using the MSAP analysis showed a predominant hypomethylation in a tolerant rice accession under drought stress (Gayacharan and Joel, 2013). Furthermore, Abid et al (2017) recently noticed that drought stress reduces the methylation level in two faba bean genotypes, irrespective to their tolerance level. These contrasting reports imply that different methylation mechanisms for drought tolerance exist in plant species.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Many studies have found that degree and state of DNA methylation in plant would change under drought stress, low temperature, high salt and other conditions [32,33], especially change of methylation state in the promoter of gene [34]. Under drought stress, methylation level altered in the promoter of DREB2, DREB6 and Wdreb2, compared with the control, methylation level in DREB2 and DREB6 promoter decreased as stressed for 2h, then increased along with the increase of stress time, which was opposite in Wdreb2 promoter.…”
Section: Discussionmentioning
confidence: 99%